Trichoderma species compatibility for production and wilt chili biocontrol - Gallegos-Morales, Gabriel; Espinoza-Ahumada, César Alejandro; Figueroa-Reyes, Jesica; Méndez-Aguilar, Reinaldo; Rodríguez-Guerra, Raúl; Salas-Gómez, Alma Leticia; Peña-Ramos, Fidel Maximiano (Ecosistemas y Recursos Agropecuarios, 2022)
Trichoderma species have been shown to have antagonistic activity against Fusarium oxysporum and Rhizoctonia solani, which cause chili wilt. The objective was to determine the compatibility of four species of Trichoderma and its effect on the control of pepper wilt and crop yield. In the laboratory, compatibility tests were carried out for Trichoderma asperellum (TA), T. harzianum (THZ), T. lignorum (TL) and T. yunnanense (TY). In the field, the effect of the application of species to control wilting and crop production were evaluated. The TA-TL, TA-THZ and TA-TL-THZ strains were compatible and expressed an increase in yield per plant of up to 86%, the number of fruits by 79%, and a decrease in the incidence (71%) and severity of the disease. disease (59%). T. lignorum expressed to be compatible with the other species of Trichoderma evaluated, in addition to increasing the yield and control of the disease.